Effects of Chronic Asprosin Administration on Metabolic Hormones in Male Rats - Kacar, E.; Kocoglu, S. R.; Zorlu, G.; Tan, F.; Avcu, G. G.; Zorlu, O.; Kelestimur, H. (Wiley, 2022)
[Abstract Not Available]